Vestibular Disorders after Stapedial Surgery in Patients with Otosclerosis. (19th January 2016) - de Vilhena, Ditza; Gambôa, Inês; Duarte, Delfim; Lopes, Gustavo
Abstract : Introduction and Objectives . Vertigo is a described complication of stapedial surgery. Many studies have been conducted to assess the improvement of hearing loss, but there are few studies that assess vestibular function after stapedial surgery. The aim of this study was to evaluate the presence and characterize the vertigo after stapedial surgery. Methods . We conducted a prospective observational study. Patients undergoing stapedial surgery in our hospital between October 2013 and December 2014 were invited to participate. The vertigo was assessed before and 4 months after surgery, using the Dizziness Handicap Inventory. Results . We included 140 patients in the study. 12 patients (8.6%) reported vertigo before surgery, and all of them denied vertigo after surgery. 36 patients (25.7%) reported vertigo four months after surgery, and none of them had vertigo before surgery. Postoperative total scores in patients with vertigo ranged between 2 and 18 points. Conclusion . The study shows that vestibular disorders may remain after the immediate postoperative period and reinforces the need for clarification of the patient in the informed consent act.